Interactive gerontechnology for fall prevention in the elderly: a descriptive study - Juliana Cunha Maia; Jamylle Lucas Diniz; Caroline Ribeiro de Sousa; Francisco Gerlai Lima Oliveira; Brenda Pinheiro Evangelista; Janaína Fonseca Victor Coutinho; Marília Braga Marques; Rachel Gabriel Bastos Barbosa (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to develop interactive gerontechnology for the prevention of falls in the elderly at home. Methods: an exploratory and descriptive study that consisted of gerontechnology development and evaluation by experts and the target audience. For evaluation, researchers used the Agreement Index (AI), considering values greater than 80%. Results: the three-dimensional virtual scale model was elaborated through the SketchUp program, with the distribution of rooms and floors, constituting Prototype 1 (P1). Fifty-four judges evaluated the P1, and all presented agreement above the established, with a minimum AI of 88% and a maximum of 100%, producing Prototype 2 (P2). Thirty elderly participants from a philanthropic institution evaluated Prototype 2. On all items, AI ranged from 83% a 100%, resulting in the final version. Conclusions: the product of this research reveals itself as an innovative and scientifically based tool aimed at preventing falls in the elderly.